THE EFFECTIVENESS OF ISLAMIC LITERATURE TEXT MODEL IN READING SKILLS OF THE COVID-19 PANDEMIC TIME - Husin, Ahmad; Wapa, Andi (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
National Education aims to educate the nation and develop a whole Indonesian man who is balanced, harmonious, in harmony in his life and life as well as physically and mentally healthy. To achieve this goals, education is needed that is very concerned about the needs of students. The students' needs are intended forms of innovative learning media. Literary works (Islamic literary texts) are expected to be used to awaken the public (readers) to return to their nature, on the right path. Literature is an expression of society, therefore the emergence of a literary work is closely related to the problems that arise at that time. In addition, literature can serve as a work of art that can be used to entertain readers. In a novel there must be a variety of expressions, namely the expression or process of stating. In this analysis, there are findings about charting and data codification of focus on religious values that can be applied in the Islamic literary text model in learning reading skills in online learning during the Covid-19 pandemic. The Islamic literary text used is the novel of Api Tauhid by Habiburrahman El Shirazy. The results of the preliminary study indicate that the failure in language learning, especially reading skills, has been caused by the approach used not being focused on efforts to create communicative abilities / skills. Reading skills are carried out through a one-way approach. Students are asked to read the text, do the exercises, and end by discussing the results of student work. Such a model is very irrelevant to the level of interest of students in learning to read. What students need how they become reliable readers. The next,